Fine periodic nanostructure formation on stainless steel and gallium arsenide with few-cycle 7-fs laser pulses - Ishihara, Akihiro; Miyaji, Godai (Frontiers in Nanotechnology, 2023)
We report the fine periodic nanostructure formation process on metal and semiconductor surfaces in air with few-cycle 7-fs laser pulses and its physical mechanism. Using appropriate peak power densities and scanning speeds for the laser pulses, nanostructures could be formed on stainless steel and gallium arsenide (GaAs) with periods of 60-110 nm and 130-165 nm, respectively, which are 1/5-1/4 of the period of nanostructures formed with 100-fs laser pulses. The periodicity can be explained as arising from the excitation of short-range propagating surface plasmon polaritons, and the observed periods are in good agreement with the model calculation results.